Impurity and sin in ancient Judaism - Klawans, Jonathan (Oxford University Press, 2000)
Jonathan Klawans shows how the link between moral impurity and physical defilement, as understood by the ancient Hebrews, can be followed through to St Paul and the Christian era when the need for ritual purity was finally rejected.